2018
DOI: 10.1039/c8sc00678d
|View full text |Cite
|
Sign up to set email alerts
|

Thinking outside the box: placing hydrophilic particles in an oil phase for the formation and stabilization of Pickering emulsions

Abstract: Unconventionally, by placing hydrophilic particles in an oil phase before emulsification, the energy barrier is successfully eliminated and Pickering emulsions are easily formed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 69 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…It was reported that the dispersed phase can influence the interfacial activity and hydrophobicity of particles [16,39] . After the dispersion of microgels in the oil phase in the presence of 20 vol% octanol, inverse W/O Pickering emulsions could be successfully prepared (Figures 2e and g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the dispersed phase can influence the interfacial activity and hydrophobicity of particles [16,39] . After the dispersion of microgels in the oil phase in the presence of 20 vol% octanol, inverse W/O Pickering emulsions could be successfully prepared (Figures 2e and g).…”
Section: Resultsmentioning
confidence: 99%
“…[38] It was reported that the dispersed phase can influence the interfacial activity and hydrophobicity of particles. [16,39] After the dispersion of microgels in the oil phase in the presence of 20 vol% octanol, inverse W/O Pickering emulsions could be successfully prepared (Figures 2e and g). Water droplets laden with octanol-swollen 4VP microgels had an average diameter of 53 μm (Figure 2f), which was smaller than that of the water droplets stabilized by octanol-swollen MAA microgels (160 μm, Figure 2h).…”
Section: Emulsifying Capability Of Microgels In Stabilizing Pickering...mentioning
confidence: 99%
“…37,44 Dispersing the hydrophilic particles in the oil phase rather than in the water phase initially was a novel approach for the formation and stabilization of Pickering emulsion. 45 In our previous study, the influence of the initial phase of surfactants was ignored in the formation process of O/W nanoemulsions by phase inversion temperature methods. These nanoemulsions using D230−2OA surfactant with propylene oxide (PO) units were unstable against Ostwald ripening.…”
Section: ■ Introductionmentioning
confidence: 99%
“…High resistance to coalescence is an obvious advantage of Pickering emulsions compared to traditional ones. To circumvent the use of synthetic surfactants for sustainable and ecological reasons, the “surfactant-free” Pickering emulsions came into renewed interest in particular foods, pharmaceuticals, and cosmetics. , Especially, highly concentrated emulsions with the volume ratio of the internal phase higher than 74% are usually referred to as high internal phase emulsions . Except avoiding the utilization of considerable quantities of surfactants (5–50%, v/v), Pickering HIPEs also possess apparent advantages compared with conventional ones in such aspects as stability against coalescence, environmental effects, texture modification, calorie reduction, product safety, etc.…”
Section: Introductionmentioning
confidence: 99%